Design and Build an Assessment Platform by Inserting Moodle-Based Cryptographic Methods - Pradeka, Deden; Adiwilaga, Anugrah; Agustini, Devi Aprianti Rimadhani; Suheryadi, Adi; Nuriman, Rizki (Jurnal Nasional Teknologi dan Sistem Informasi, 2023)
The use of digital platforms in the learning process is increasing, especially in the context of assessment activities. In this context, it is essential to realize that digital platforms can be subject to attack or fraud by irresponsible parties. It is due to the presence of sensitive data and/or restricted to a limited number of authorized persons. Therefore, the protection of data and its security in using digital platforms is very important. To enhance this layer of security in data protection, cryptographic methods play a crucial role in maintaining information security. By applying cryptographic methods to learning platforms for assessment purposes, we can increase the security and integrity of the data involved in the assessment process. This research aims to produce a plugin that can be used on a Moodle-based Learning Management System (LMS). This plugin will provide an additional activity in the form of an assessment activity with an essay exam type. When this plugin is used, all questions and answers will be encrypted into text that is difficult to understand by unauthorized parties when an attack attempt occurs. In this way, the learning platform for assessment purposes can safeguard and protect data from access by irresponsible parties.